Edwin Hutchins: In defense of interdisciplinary research on cognition - Miłkowski, Marcin; Witold (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2022)
The article presents the interdisciplinary approach of Edwin Hutchins, analyzing his conception of distributed cognition as probably the most important and lasting contribution of anthropology to the repertoire of theoretical tools in cognitive science. At the same time, this conception resulted in one of the most interesting relationships between cognitive science and social sciences. These relationships are made possible by the assumptions of Hutchins’ conception, which directly contribute to interdisciplinary collaboration. His account of distributed cognition has enormous potential, allowing the integration of research into cognitive and social processes. This is also because it breaks with methodological individualism.